The impact of personality on students' perceptions towards online learning - Bhagat, Kaushal Kumar; Wu, Leon Yufeng; Chang, Chun-Yen (Australasian Journal of Educational Technology, 2019)
The aim of this exploratory study was to examine the impact of five personality traits (extraversion, agreeableness, conscientiousness, neuroticism, and intellect/imagination) on the perception of students towards online learning. A total of 208 students from Taiwan (male = 96 and female = 112) with previous online course experience participated in an online survey using a bulletin board system. To measure personality traits and students’ perceptions, the Mini-International Personality Item Pool and the Perception of Students towards Online Learning instruments were used respectively. The researchers employed hierarchical regression analysis to analyse the data obtained. The results showed that two personality traits (conscientiousness and intellect/imagination) had a larger positive impact on students' perceptions towards online learning, whereas neuroticism had significantly negative effects on participants of online courses. These results provide evidence that students with different personality traits have different preferences for and experiences in online courses.